CAR T Cells Beyond Cancer: Hope for Immunomodulatory Therapy of Infectious Diseases - Seif, Michelle; Einsele, Hermann; Löffler, Jürgen (Frontiers in Immunology, 2019)
Infectious diseases are still a significant cause of morbidity and mortality worldwide. Despite the progress in drug development, the occurrence of microbial resistance is still a significant concern. Alternative therapeutic strategies are required for non-responding or relapsing patients. Chimeric antigen receptor (CAR) T cells has revolutionized cancer immunotherapy, providing a potential therapeutic option for patients who are unresponsive to standard treatments. Recently two CAR T cell therapies, Yescarta® (Kite Pharma/Gilead) and Kymriah® (Novartis) were approved by the FDA for the treatments of certain types of non-Hodgkin lymphoma and B-cell precursor acute lymphoblastic leukemia, respectively. The success of adoptive CAR T cell therapy for cancer has inspired researchers to develop CARs for the treatment of infectious diseases. Here, we review the main achievements in CAR T cell therapy targeting viral infections, including Human Immunodeficiency Virus, Hepatitis C Virus, Hepatitis B Virus, Human Cytomegalovirus, and opportunistic fungal infections such as invasive aspergillosis.